A theory of economic growth : - Croix, David de La (Cambridge University Press, 2002)
Inter-generational transfers are at the center of economic policy debates today. Reducing public debt; financing social security; taxing capital and bequests; and designing the education system imply substantial inter-generational transfers. The tool that economists employ to analyze these issues is the overlapping generations model, which reflects the different periods of life. When the model includes capital accumulation, it also allows researchers to formalize the development of an economy, relating its growth path to the savings behavior of young agents. The aim of this book is an in-depth analysis of this model that includes its major policy implications.